Galactic dynamics in the presence of scalaron: a perspective from f(R) gravity - Mohan, Gayatri; Dev Goswami, Umananda (Physica scripta, 2024)
We consider f ( R ) modified gravity theory incorporating the chameleon mechanism to address galactic dynamics. By employing the metric formalism and utilizing a conformal transformation, we simplify the field equations and describe the extra degree of freedom f R via a scalar field (scalaron) with chameleonic behavior. A recently proposed f ( R ) model is analyzed to illustrate this behavior effectively. Subsequently, the rotational velocity equation including the scalaron’s contribution is derived for a test particle in a static, spherically symmetric spacetime. Then we generate rotation curves and fit them to observational data of thirty seven galaxies using two fitting parameters, M 0 and r c , the total mass and core radius of a galaxy respectively.